Immunoreactive cutaneous sporotrichosis, - Gustavo de Sá Menezes Carvalho; John Verrinder Veasey (Sociedade Brasileira de Dermatologia, 2020)
Abstract Sporothrix spp. infection can occur through the inoculation of the organism in the skin through direct contact with the soil (sapronotic infection), through contact with animals, such as infected cats and dogs (zoonotic infection), or less frequently via inhalation. With a subacute or chronic evolution, approximately 80% of patients affected by the disease present with the lymphocutaneous form; episodes associated with a hypersensitivity reaction are rare. The authors report the case of a 12-year-old child with immunoreactive sporotrichosis manifested clinically as erythema nodosum lesions in the lower limbs, associated with an ulcerated lesion in the left arm.